LPA is a chemorepellent for B16 melanoma cells: action through the cAMP-elevating LPA5 receptor - Jongsma, Maikel; Matas-Rico, Elisa; Jalink, Kees; Moolenaar, Wouter H; Rzadkowski, Adrian (PLOS One, 2011)
Lysophosphatidic acid (LPA), a lipid mediator enriched in serum, stimulates cell migration, proliferation and other functions in many cell types. LPA acts on six known G protein-coupled receptors, termed LPA1–6, showing both overlapping and distinct signaling properties. Here we show that, unexpectedly, LPA and serum almost completely inhibit the transwell migration of B16 melanoma cells, with alkyl-LPA(18∶1) being 10-fold more potent than acyl-LPA(18∶1). The anti-migratory response to LPA is highly polarized and dependent on protein kinase A (PKA) but not Rho kinase activity; it is associated with a rapid increase in intracellular cAMP levels and PIP3 depletion from the plasma membrane. B16 cells express LPA2, LPA5 and LPA6 receptors. We show that LPA-induced chemorepulsion is mediated specifically by the alkyl-LPA-preferring LPA5 receptor (GPR92), which raises intracellular cAMP via a noncanonical pathway. Our results define LPA5 as an anti-migratory receptor and they implicate the cAMP-PKA pathway, along with reduced PIP3 signaling, as an effector of chemorepulsion in B16 melanoma cells.
Keywords: Melanoma; Lysophosphatidic acid; cell migration; LPA5 receptor; G protein-coupled receptors; chemorepulsion